Impact Of Hypotensive Action Of Angiotensin Converting Enzyme Inhibitor On Ovarian-Intraovarian Blood Flow And Follicles Development In Goats Hormonally Stimulated With Repeated Fsh-Ecg Treatment - Moreno, Maria Eugenia; Bravo, Pamela Angela; Fernandes, Denilsa Pires; Fernandes, César Carneiro Linhares; Rossetto, Rafael; Cavalcanti, Camila Muniz; Montenegro, Assis Rubens; Teixeira, Dárcio Ítalo Alves; Rondina, Davide (Acta Scientiae Veterinariae, 2020)
Background: Recent evidence shows that the renin-angiotensin system (RAS) participates in important reproductive processes, such as steroidogenesis, folliculogenesis, oocyte maturation and ovulation. Several studies have proposed to use an angiotensin-converting enzyme (ACE) as a RAS modulator, aiming to improve reproductive efficiency, however, the presence of the main components of this system in reproductive tissues still need to be further investigated, since the physiological functions seem to be species-specific. The aim of this study was to assess the impact of enalapril-maleate, an ACE inhibitor, during repeated gonadotropins treatment on ovarian blood flow and follicular development in goats. Materials, Methods and Results: Twenty Anglo-Nubian cross-bred goats were equally grouped according to parity (n=10/group): nulliparous and multiparous parity. In each group, five animals were randomly selected to receive 0.4 mg.kg-1 of enalapril-maleate during 11 days of estrus synchronization and gonadotropins treatments. The other animals received the same volume of saline solution. Estrus synchronization of all goats was made by intramuscular administration of PGF2α analog, followed 48 h later by intravaginal insertion of a controlled internal drug release device. Forty-eight hours after device withdrawal, a single dose of 60 mg of FSH plus 300 UI of eCG was administered and repeated every 4 days to complete 3 treatments. Transrectal ultrasonography was performed using pulsed and color Doppler to evaluate Doppler velocimetrics parameters of the ovarian artery and intraovarian blood flow, respectively, and B-mode real-time ultrasound scanner to evaluate the follicular development. In the females treated with enalapril-maleate was observed a significant reduction of systolic and diastolic peak, without difference according to parity. In addition, in the third session of hormonal stimulation, only the groups (nulliparous and multiparous) not treated with enalapril maleate had a significant increase in the intraovarian blood flow (Doppler area). In treated group was also found a greater number of small follicles, a lower proportion of follicle ≥ 5 mm and a smaller follicular size. In the same group, the nulliparous females had a lower proportion of large follicles compared to the saline group, otherwise, there were no differences between the treatments in multiparous goats. In the group treated with enalapril maleate, higher number of large follicles was observed in multiparous animals than in the nulliparous ones. Discussion: In vivo and in vitro studies have shown clear effects of RAS modulation on reproductive aspects. Our results confirmed the hypotensive effect of enalapril maleate on the ovarian artery and intraovarian blood flow, also showing that the administration of the drug reduced the process of follicular depletion and the growth of large follicles. These findings suggest that the hypotensive effects observed in our experiment, result from the treatment with the ACE inhibitor, and that this alteration in hemodynamic parameters may be the main responsible for the lower follicular response observed in animals treated with enalapril-maleate. We suggest that further studies are necessary to elucidate possible effects of the administration of an ACE inhibitor on ovarian activity, especially in the expression of genes associated with follicular, oocyte and embryonic development. Finally, the study conclude that the administration of enalapril-maleate in our experimental condition exhibit a hypotensive effect on ovarian circulatory system but did not show to promote a real benefit of follicular development in goats.